SOSIALISASI DAMPAK NEGATIF INSEMINASI BUATAN PADA SAPI BALI DAN CARA MENCEGAHNYA - Lalu Ahmad Zainuri; Rodiah Rodiah; Adji Santoso Dradjat; Lukman HY; Eny Yuliani (Jurnal Abdi Insani, 2023)
Artificial insemination in Bali cattle provides significant value to increase Bali cattle productivity. However, the negative impacts should not be ignored. Therefore, this community service aims to socialize the negative impacts of artificial insemination and how to prevent it on cattle. This activity was carried out in Sapit village, Suela subdistrict, East Lombok district, NTB. The form of activity is in class session, question and answer session, followed by a visit to the group's cattle housing. This activity was attended by 26 farmers representing 6 group hausing in Sapit village, 4 inseminators and 2 paramedics from the Suela sub-district health center. The evaluation results show that the community service material received a very good response from all participants. A total of 28 people (87.5%) participants stated that the topic was very useful for them. From the entire series of processes and implementation of community service, the team has discussed and evaluated various supporting factors, inhibiting factors and follow-up plans. The inhibiting factor was the bad experience of farmers because some of the cow had experienced dystocia and uterine prolapse so they were still hesitant to carry out AI on their cows. However, after being given lectures and questions and answers by the service team, farmers became more aware of how to prevent reproductive disorders in their cows. Therefore, based on the results of the evaluation carried out after the activity ended, it was found that all participants (100%) stated that they had no doubts and would continue to carry out AI on their cattle.